Research and Practical Issues of Enterprise Information Systems : 13th IFIP WG 8. 9 International Conference, CONFENIS 2019, Prague, Czech Republic, December 16-17, 2019, Proceedings /: 13th IFIP WG 8. 9 International Conference, CONFENIS 2019, Prague, Czech Republic, December 16-17, 2019, Proceedings. (2019) - Unknown
No abstract available